2021
DOI: 10.26636/jtit.2021.146020
|View full text |Cite
|
Sign up to set email alerts
|

LEES: a Hybrid Lightweight Elliptic ElGamal-Schnorr-Based Cryptography for Secure D2D Communications

Abstract: Device-to-device (D2D) communications in 5G networks will provide greater coverage, as devices will be acting as users or relays without any intermediate nodes. However, this arrangement poses specific security issues, such as rogue relays, and is susceptible to various types of attacks (impersonation, eavesdropping, denial-of-service), due to the fact that communication occurs directly. It is also recommended to send fewer control messages, due to authenticity- and secrecy related prevailing requirements in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Relay attacks are used to resend a legitimate user's authentication signal to gain network access without decrypting the message content. The attacker may succeed when no protection or additional checks are implemented [72].…”
Section: Access Attacksmentioning
confidence: 99%
See 3 more Smart Citations
“…Relay attacks are used to resend a legitimate user's authentication signal to gain network access without decrypting the message content. The attacker may succeed when no protection or additional checks are implemented [72].…”
Section: Access Attacksmentioning
confidence: 99%
“…The greater the size, the greater the number of research papers identified. The solutions addressing different threats focused on design, implementation, security analysis, and security assurance frameworks [13,24,32,50,67,[80][81][82][83][84]; systems for security assurance [47], intrusion detection [29] and security incident management [85]; approaches/mechanisms for security [7,25,28,40,41,43,45,48,[86][87][88][89][90][91] and remote diagnostics [92]; schemes for security assurance [72,73,[93][94][95]; protocols for security assurance [8,16,39,53,62,63,[96][97][98][99][100][101]; algorithms for security assurance [102]; models/algorithms for securi...…”
Section: Proposed Solutionsmentioning
confidence: 99%
See 2 more Smart Citations